Budget Politics: A Case Study of Actor Relations in the Formulation of Local government budget Policy in Polewali Mandar Regency in 2025 - Aco Nata Saputra; Achmad Fauzi Kusmin; Citra N Fariaty; Andi Nur Fiqhi Utami (Journal of Law, Politic and Humanities, 2025)
Budget politics is a strategic part of regional development. Sustainable regional development is closely related to the Regional Expenditure Budget. This study seeks to reveal how actor relations are in the formulation of Local government budgetPolicy in Polewali Mandar Regency in 2025, the actors in question are the executive represented by the Regional Government Budget Team and the legislative represented by the Local Legislative Assembly Budget Agency. It is interesting because the preparation of the 2025 Local government budgetwill be carried out in 2024 which is a political year and a year of leadership transition with the simultaneous Legislative and Regional Elections. This research uses a qualitative approach that with the type of case study of the object or social reality being researched, it is holistic, complex, dynamic and full of meaning. The results of the study found that the actors involved in the preparation of the Regional Expenditure Budget are very dominated by formal executive and legislative actors, there is no room for informal actors. The transition period of executive leadership and legislative membership transition is not an obstacle to formulating the 2025 Local government budget. Compromise and Consensus are produced in their entirety by prioritizing the principle of togetherness and the welfare of citizens (constituents). The Compromise aspect in the preparation of the 2025 Local government budgetis carried out by means of formal lobbying between the executive and the Legislature. The Consensus aspect was reached several agreements on efforts to make the Local government budgethealthy (no deficit), the alignment of the Local Government Budget with the Local go government medium term (5 year) development plan and Local Government Budget as much as possible in line with the visions and missions of the elected regent.